The Many Facets of EU Soft Law - Láncos Petra Lea (A Pázmány Péter Katolikus Egyetem Jog- és Államtudományi Karának Könyvei. Jogtudományi Monográfiák, 2022)
In 2016 I joined the group of researchers working on the project European Administrative Space at the Deutsches Forschungsinstitut für öff entliche Verwaltung (FÖV) located at the Deutsche Universität für Verwaltungswissenschaften in Speyer, Germany. In my three years at the FÖV I tried to discern the room for manoeuvre or leeway enjoyed by Member States in the face of European soft law sources (‘EU soft law and national scope of action’). Preparing for my research, I quickly came to understand that the study of EU soft law was most concerned with the ontology and taxonomy of this particular category of legal sources. Abundant academic literature revolves around solving the conundrum of separating hard law from soft law, and the myriad non-binding measures employed by EU institutions and bodies continues to confound legal scholars. Meanwhile, the incremental proliferation of such measures to facilitate the effi cient operation of EU policies also makes academic inquiry into novel areas of research necessary, such as the possible eff ects of EU soft law and the implementation and consideration of EU soft law within the Member States. I was lucky enough to have been given wide berth to design my research agenda within the European Administrative Space project and for having been invited to contribute to the Soft Law Research Network (SoLaR) focusing of the use of soft law by national courts and administrations. This enabled me to both approach the study of EU soft law from a broader perspective, trying to summarize existing EU soft law-related research, to map new areas of inquiry, including the confusing phenomenon of directive-like recommendations, and to focus on the national reception and use of EU soft law, my actual fi eld of research at FÖV. This volume is an edited monograph containing my fi ndings on EU soft law and its implementation (with a particular focus on Hungary) published during my work as a researcher at the FÖV, as well as the following years. It is an attempt at capturing in this moment of time the nature and function of this elusive and ever changing species of legal sources: the non-binding measures of EU law.